Глѥть Aр‹ї›стотель. Further examples of Aristotelian scholia in Serbian Church-Slavonic translation of Gregory Palamas’ “Apodictic treatises on the procession of the holy spirit” - Knežević Mikonja (Glasnik Etnografskog Instituta SANU)
The Serbian Church-Slavonic translation of Gregory Palamas’ “Apodictic Treatises on the Procession of the Holy Spirit” contains a large number of scholia. Their main intention is to clarify the Orthodox teaching on the procession of the Holy Spirit. In some of them, the translator, both in terms of content and origin, brings to light certain segments from Aristotle’s philosophy that are only implicitly present in the basic text. In this paper I give some of these scholia in the original and Modern Serbian translation, along with my own comments regarding each of them.